1999
DOI: 10.1210/me.13.7.1119
|View full text |Cite
|
Sign up to set email alerts
|

The Adenovirus E1A Protein Is a Potent Coactivator for Thyroid Hormone Receptors

Abstract: The thyroid hormone receptors interact with several different cofactors when activating transciption. In this study, we show that the adenovirus E1A oncoprotein functions as a strong coactivator for the thyroid hormone receptor (TR), and that TR and E1A synergistically activate transcription via direct (DR4) or palindromic (IRO) hormone-responsive sites. Cotransfection experiments using different isoforms of the chicken TR and E1A show synergistic, ligand-enhanced transactivation. This transactivation is accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This activation of transcription requires acetyltransferase activity. E1A is known to influence transcriptional activation by nuclear receptors (Berkenstam et al ., 1992; Meyer et al ., 1996; Kurokawa et al ., 1998; Wahlstrom et al ., 1999). We make use of E1A to explore further the role of p300 and acetylation in transcriptional control by the TR in chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…This activation of transcription requires acetyltransferase activity. E1A is known to influence transcriptional activation by nuclear receptors (Berkenstam et al ., 1992; Meyer et al ., 1996; Kurokawa et al ., 1998; Wahlstrom et al ., 1999). We make use of E1A to explore further the role of p300 and acetylation in transcriptional control by the TR in chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…While these findings appear to differ from the yeast studies [20, 52] and the transient transfection studies in mammalian cell cultures, a careful analysis suggests that results are consistent in several key aspects. First, in the absence of T3, E1A enhanced transcription by unliganded TR in all three systems (In the transient transfection assays [51], although the authors focused the discussion on the effects in the presence of T3, there was clear upregulation of the reporter gene expression in the absence of T3. In fact, the fold enhancement in the absence of T3 appeared to be similar than that in the presence of T3).…”
Section: Discussionmentioning
confidence: 99%
“…These interesting findings may help to explain some of the differences observed in the earlier studies in yeast and JEG cells. First, although in vitro GST-fusion protein pull-down assays suggest that E1A has multiple regions that bind to TR [20, 51, 52], a yeast two-hybrid assay showed that the N-terminal 29 amino acids were essential for the interaction in vivo [20] and further studies identified a leucine-rich CoR-NR box consensus motif in the N-terminal (20-28) amino acids of E1A as well as in the interacting domains of N-CoR and SMRT [52]. Our transcription assay in vivo also showed a requirement for this region for interaction with TR in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TR functions by recruiting cofactors. Many such cofactors have been isolated and characterized (Burke and Baniahmad, 2000; Glass and Rosenfeld, 2000; Huang et al, 2003; Ito and Roeder, 2001; Jones and Shi, 2003; McKenna et al, 1999; McKenna and O'Malley, 2001; Meng et al, 2003; Rachez and Freedman, 2000; 2001; Sato et al, 2009; Wahlstrom et al, 1999; Xu et al, 1999; Zhang and Lazar, 2000). In the absence of TH, TR recruits corepressors, such as the highly related proteins SMRT and N-CoR, which form multimeric complexes containing histone deacetylases (HDACs) (Burke and Baniahmad, 2000; Glass and Rosenfeld, 2000; Jones and Shi, 2003; Zhang and Lazar, 2000) (Fig.…”
Section: Mechanisms Of Th Actionmentioning
confidence: 99%